2013
DOI: 10.1002/chem.201203834
|View full text |Cite
|
Sign up to set email alerts
|

Designed Synthesis of Well‐Defined Pd@Pt Core–Shell Nanoparticles with Controlled Shell Thickness as Efficient Oxygen Reduction Electrocatalysts

Abstract: Improving the electrocatalytic activity and durability of Pt-based catalysts with low Pt content toward the oxygen reduction reaction (ORR) is one of the main challenges in advancing the performance of polymer electrolyte membrane fuel cells (PEMFCs). Herein, a designed synthesis of well-defined Pd@Pt core-shell nanoparticles (NPs) with a controlled Pt shell thickness of 0.4-1.2 nm by a facile wet chemical method and their electrocatalytic performances for ORR as a function of shell thickness are reported. Pd@… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
71
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 49 publications
3
71
1
2
Order By: Relevance
“…These Pt 3 Co/C catalysts exhibited over 200% increase in mass activity and over 300% increase in specfic activity when compared with disordered Pt 3 Co alloy nanoparticles as well as Pt/C particles. In addition to Co, other metals, such as Au, 284 Ag, 285 Cu, 214 Ni, 382 and Pd, 383,384 have also been used as the core inside a Pt shell.…”
Section: 372−375mentioning
confidence: 99%
“…These Pt 3 Co/C catalysts exhibited over 200% increase in mass activity and over 300% increase in specfic activity when compared with disordered Pt 3 Co alloy nanoparticles as well as Pt/C particles. In addition to Co, other metals, such as Au, 284 Ag, 285 Cu, 214 Ni, 382 and Pd, 383,384 have also been used as the core inside a Pt shell.…”
Section: 372−375mentioning
confidence: 99%
“…Adzic et al 17 conducted experiments using a Pt monolayer-coated metal electrode and found that the unique activities are attributed to the optimized O 2 binding strength and the d-band center position. Based on this finding, Han et al 18 synthesized a precisely controlled Pt shell with a thickness of 0.4-1.2 nm on Pd nanoparticles (NPs) of 6 nm. Furthermore, Pd@Pt NPs with a shell thickness of 0.94 nm, were found to exhibit ORR performance superior to that of commercial Pt catalysts in an HClO 4 electrolyte.…”
mentioning
confidence: 99%
“…Furthermore, Pd@Pt NPs with a shell thickness of 0.94 nm, were found to exhibit ORR performance superior to that of commercial Pt catalysts in an HClO 4 electrolyte. 18 Zhang et al successfully prepared dendritic-Pt-shell coated Pd nanostructures using a microwave method with a fixed Pd/Pt molar ratio of 1:3. 19 They found that the ORR kinetics was faster by the activity of these nanostructures than that by pure Pt nanodendrites or Pd naocubes in a 0.5 M H 2 SO 4 electrolyte.…”
mentioning
confidence: 99%
“…Core-shell catalysts that consist of an ultrathin Pt shell and a Pd core have been proposed as candidates to replace pure Pt. [6][7][8][9][10] In addition to the high Pt utilization and lower cost of the Pd core, strain and electronic effects induced by the Pd core can enhance the activity of the Pt shell for the ORR, 11 leading to a greater activity per mass of Pt than expected based on the utilization improvement alone.…”
mentioning
confidence: 99%